MENGGUGAT RELASI FILSAFAT POSITIVISME DENGAN AJARAN HUKUM DOKTRINAL - FXAdji Samekto (Jurnal Dinamika Hukum, 2012)
In the teaching of law, there is often "mistaken", that puts legal positivism (jurisprudence)  is identical with the philosophy of positivism. Legal positivism be identified as an instance of positivism philosophy intact. The study of legal positivism, in fact very closely related to the philosophy and teachings of the law from time to time. The effects of natural law in the scholastic era, then the era of rationalism and the influence of positivism in the philosophy of natural science is very attached to the legal positivism until today. Therefore not only the philosophy of positivism affecting the development of legal positivism. Based on that then the legal positivism in fact has a characteristic which is different from the social sciences. If the social sciences were developed based on the philosophy of positivism, the doctrinal teaching of the law is not entirely been developed based on the philosophy of positivism. Not all the logical positivist philosophy can be applied in the doctrinal law. Keywords : positivism, legal positivism, doctrinal